El principio de asistencia humanitaria y la mujer desplazada en Colombia (2013)
This article describes the guidelines of the international community with regardsto internal displacement and humanitarian aid principle. Also, it consolidates theposition of the Constitutional Court, based on its decisions, especially RulingT-025 of 2004 and Order 092 of 2008, with emphasis on the care and protection of displaced women, and it highlights their contribution to the design of statepolicy for the displaced.